A Study on The Seventh-Grade Teaching Speaking Methods at MTs Muhammadiyah Malang - Wati, Nisa; Setyaningrum, Rina (University of Muhammadiyah Malang, 2014)
An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show